Investigating the impact of Caspase-8 and Connexin-43 on metastasis and tumour aggressiveness in human ovarian cancer using an orthotopic mouse model - Aberoumandi, Seyed Mohsen; Justus Liebig University Giessen (My University, 2024)
Ovarian carcinoma is the leading cause of mortality among gynaecological malignancies, primarily due to late-stage diagnosis and the presence of metastatic disease. As most patients present with advanced tumours, an improved understanding of the molecular mechanisms driving tumour progression, metastasis, and therapeutic resistance is required for the development of targeted therapies. Caspase-8 (CASP8), a key regulator of apoptosis, and Connexin-43 (CX43), a gap-junction protein implicated in cell-cell communication and metastasis, have emerged as potential therapeutic targets in ovarian cancer. This PhD project aimed to investigate the functional roles of CASP8 and CX43 in ovarian cancer progression, metastasis, and response to chemotherapy using clinically relevant in vivo and in vitro models. High- grade serous ovarian cancer cell lines (OVCAR8 and OVCAR3) were engineered using CRISPR-Cas9 to generate CASP8 and/or CX43 knockout (KO) models for analysis in an orthotopic mouse model and complementary in vitro assays. In vivo, luciferase-labelled OVCAR8 KO:CASP8 cells exhibited significantly enhanced tumour growth and widespread organ dissemination compared with OVCAR8 WT, highlighting a tumour-suppressive role for CASP8. In vitro, CASP8-deficient cells displayed increased resistance to carboplatin and paclitaxel, with reduced chemotherapy- induced apoptosis relative to WT cells. Immunodetection studies revealed increased CX43 expression following CASP8 loss, suggesting functional crosstalk between these proteins. Functional assays demonstrated that CASP8 depletion enhanced invasion in OVCAR3 cells, while co-depletion of CASP8 and CX43 attenuated this phenotype; however, combined KO increased migratory capacity. Overall, these findings reveal a complex, context-dependent interaction between CASP8 and CX43 in regulating ovarian cancer invasion, migration, and therapeutic response, supporting their potential relevance as targets for improved treatment strategies.
Keywords: ddc:610; ddc:630